2018
DOI: 10.1016/j.jcct.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-based fat and muscle characteristics are associated with mortality after transcatheter aortic valve replacement

Abstract: Rapid CT-based tissue characterization is feasible in patients referred for TAVR. Decreased PM area and increased SAT density are associated with long-term mortality after TAVR, even after accounting for age, sex, BMI, and STS score. Further studies are necessary to interrogate sex-specific relationships between CT tissue metrics and mortality and whether CT measures are incremental to well-established frailty metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
2
36
2
Order By: Relevance
“… 14 Another study suggested the significant correlation of both small SAT and VAT areas with poor prognosis, and reported that the highest quartile of the CT density in SAT (but not in VAT) was an independent factor for increased mortality after TAVR. 15 Our data are in partial agreement with the results of previous studies. However, the CT area of AT differed between sexes and likely weakened the prognostic predictive value compared with CT density.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“… 14 Another study suggested the significant correlation of both small SAT and VAT areas with poor prognosis, and reported that the highest quartile of the CT density in SAT (but not in VAT) was an independent factor for increased mortality after TAVR. 15 Our data are in partial agreement with the results of previous studies. However, the CT area of AT differed between sexes and likely weakened the prognostic predictive value compared with CT density.…”
Section: Discussionsupporting
confidence: 92%
“…As we discussed, the volume and density of AT were different from those of younger patients and the western TAVR cohort. 13 , 15 , 25 Again, the age- and race-specific differences should be confirmed by further study. Third, several confounding factors were considered in the Cox regression model.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In a series of 161 consecutive pneumonectomy patients, we have previously showed that sarcopenia (defined as sex-specific total psoas area [TPA] at the 3rd lumbar vertebra level below the 33rd percentile), was an independent negative prognostic factor of long-term survival [ 8 ]. Since that publication, there has been accumulating evidence that, in cancer patients (regardless from the kind of cancer and administered treatments), sarcopenia can be better assessed by taking into account the other abdominal muscles (Total Muscular Parietal Area, TMPA) at the same level (L3), thus calculating Total Muscular Area (TMA; TMA = TPA + TMPA); TMA would have better prognostic discrimination than TPA [ 10 , 11 , 12 ]. Furthermore, technological evolutions allow easy calculation by a computed tomography-scan (CT-scan) of muscular fat content, allowing to take into account only the muscular part of each muscle, in the idea that muscular fat infiltration (i.e., myosteatosis) could impact the outcome [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%